Satisfação dos clientes no setor bancário e a influência na geração de negócios - Silva, Jânio da Trindade (2022)
Customer satisfaction has been a constant search for companies that seek to remain competitive in the market and, in the banking sector, the perception of quality and customer satisfaction are fundamental elements for this competitiveness. This dissertation deals with customer satisfaction in the banking sector, using the Net Promoter Score (NPS) as a metric to measure bank customer satisfaction. In this study, we seek to analyze the NPS indexes of the main relationship bank of the respondent customers, both in the analysis of the General NPS, and also in the analysis of the dimensions that influence NPS, which were divided into four parts: Structure and ambience; Relationship and Service; Financial Products and Services; and Service Channels. It is a descriptive research with a quantitative approach and using bibliographic and documental research. The survey was carried out through an online questionnaire, by Google Forms, obtaining 177 respondents distributed in all regions of the country and from several financial institutions. Based on factorial and econometric analysis, it was observed that the extracted data present high reliability and sampling adequacy, according to Cronbach's Alpha, KMO (Kaiser-Meyer-Olkin) measures and and Bartlett’s sphericity test.